Noun as Modifier in Nominal Group: a Functional Grammar Approach - CM Simatupang, Ervina; Dahlia, Anum (International Journal of Engineering and Technology, 2018)
To get comprehensive understanding about the meaning of a nominal group, we need to study the components forming the nominal group structure. The structure of nominal group consists of Head and Modifier. Head is the matter being talked, and it is realized by noun. Modifiers are words which modify the Head, and they are realized by word classes of determiner, numeral, adjective, and noun. Noun as a Head in nominal group is a rule as the theory says nominal group is a group of words with a noun as the headword, but noun as a modifier word deserves researching. The objective of this paper is to know the function and the meanings of noun as modifying component in nominal group structure. To obtain the function and the meanings of it, the theories of Functional Grammar are used, since the theories discuss the structure of nominal group comprehensively. The method used in this research is the qualitative method. The results of this research are noun as modifier has function to classify the Thing into its subclass, then it is labeled as Classifier, and the meanings expressed by classifier are expressing purpose and function, status, scope, mode of operation, and origin.Â